Topics in the Theory Of Chemical and Physical Systems Proceedings of the 10th European Workshop on Quantum systemsin chemistry and physics held at Carthage, Tunisia, in September 2005 - Lahmar, Souad; Maruani, Jean.; Wilson, Stephen; Delgado-Barrio, Gerardo; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Topics in the Theory of Chemical and Physical Systems is a collection of 14 selected papers from the scientific presentations made at the 10th European Workshop on Quantum Systems in Chemistry and Physics held at Carthage, Tunisia, in September 2005. This book encompasses a spectrum of topics in which emphasis is placed on theoretical methods in the study of chemical and physical properties of various systems: Advanced Methodologies Interactions and Clusters Excited States and Condensed Matter This volume is an invaluable resource for all academics and researchers interested in theoretical, quantum or computational chemistry, physical chemistry and chemical physics, particularly molecular structure and spectroscopy, interactions and complexes. It presents a selection of some of the most advanced methodologies, results and insights in these various areas.
Advanced Methodologies -- Literate many-body perturbation theory programming: Third-order"ring" diagrams -- Multicomponent many-body perturbation theory for the simultaneous description of electronic and nuclear motion: Towards a practical implementation using literate programming methods -- Renormalized coupled-cluster methods: Theoretical foundations and application to the potential function of water -- Hyperspherical and related types of coordinates for the dynamical treatment of three-body systems -- On the time-dependent solutions of the Schrödinger equation -- Interactions and Clusters -- An improved 6-D potential energy surface for ammonia -- A review on gold-ammonia bonding patterns -- Potential energy surfaces and dynamics of He n Br2 van der Waals complexes -- Theoretical treatment of charge transfer processes: From ion/atom to ion/biomolecule interactions -- Excited States and Condensed Matter -- Shell effects and homothetic expressions for electron relaxation and other corrections to 2p-core ionization energies and spin-orbit splitting for atoms from Cl to Ba -- On the role of electronic molecular states of high spin multiplicity -- Ab initio characterization of electronically excited metastable states of S2 - -- An extensive study of the prototypical highly silicon doped heterofullerene C30Si30 -- Theoretical study of the magnetism in molecular crystals using a first-principles bottom-up methodol.
Keywords: CHEMISTRY; CHEMISTRY, PHYSICAL ORGANIC; QUANTUM THEORY; MATERIALS; CHEMISTRY; PHYSICAL CHEMISTRY; THEORETICAL AND COMPUTATIONAL CHEMISTRY; MATERIALS SCIENCE, GENERAL; QUANTUM PHYSICS; ATOMIC/MOLECULAR STRUCTURE AND SPECTRA; ATOMIC, MOLECULAR, OPTICAL AND PLASMA PHYSICS